Uma sequência didática como ferramenta metodológica para o ensino da classe Amphibia: conhecer para conservar - Fernandes, Ednuzia Ferreira (2024)
Amphibians are a very diverse group of animals, and Brazil is the country with the greatest biodiversity of these animals. However, evidence suggests that these animals are in danger of extinction worldwide, with the main contributing factors being habitat fragmentation, global warming, and the increased incidence of ultraviolet radiation. Given this scenario, it is important to study the conservation of amphibians and develop actions that raise awareness among young people in the school environment, since this is a space for reflection and knowledge building. This research aimed to evaluate the pedagogical potential of a didactic sequence aimed at teaching content related to amphibians and their ecological importance to secondary school students. To this end, a pedagogical intervention-type study was carried out, which was preceded by an initial exploration of the problem and had a qualitative approach. The participants in this research were students in the second year of secondary school at a fulltime state secondary school located in the city of Cariús in the state of Ceará. The proposal included the preparation of a Didactic Sequence, which was distributed over eight lessons to work on the theme. The data were collected through a projective interview and three structured questionnaires and analyzed using the content analysis technique. Tools such as Google Drive, Google Spreadsheets, and Google Documents were also used to facilitate the categorization and organization of the data. The research was guided by Resolution 510 of April 7, 2016 of the National Health Council (CNS) of the Ministry of Health (MS), which is a document that deliberates on the norms, rules, and recommendations for the development of scientific research involving human beings. Based on the approaches taken, it was noted that the teaching of amphibians has gaps when it comes to approaching the subject linked to the importance of these animals for ecosystems. It was also realized that, in general, the research objectives were achieved, and the activities developed were positive for learning and for arousing students' interest in the subject. However, the research proved to be relevant for bringing knowledge to students, bringing concepts closer to their reality, and providing materials and methods that can be used by teachers to teach amphibians.